CO 8 - THE IMPACT OF NEURAXIAL ANESTHESIA VERSUS GENERAL ANESTHESIA ON HIP FRACTURE PATIENTS - Helena Silva1; Sancha Santos1; Joaquim Borba1; Tiago do Nascimento Cabral1; António Paiva1; Cecília Dias1 (Journal of the Portuguese Society of Anesthesiology, 2023)
.